Income Analysis of Clothing Merchants in Langsa Town Square - Dayyan, Muhammad; Anisa, Nur; Pospos, Ade Fadilah (Jurnal Investasi Islam, 2024)
This article aims to analyze the income of clothing traders in Langsa Town Square (LATOS). After conducting a survey of 87 clothing traders in LATOS through questionnaires and carrying out multiple linear regression using the SPSS version 20.0 program, it was found that simultaneously the income of clothing traders in LATOS was influenced by capital, location and promotion with a sig value of 0.000 <0.05. So if the trader increases capital by 1%, it is predicted that income will increase by 34%. Then, if the location is easier to reach by the community, income will increase by 17%. And if the merchant increases the promotion by 1%, the income will increase by 14% assuming a fixed capital and location. The implication of the results of this study is that financial institutions need to provide easy access to capital for traders to add more product variations to selling clothing. Langsa City Government needs to improve and complete facilities at LATOS such as parking lots.